A Numerical Method for Solving Fractional Differential Equations by Using Neural Network - Haidong Qu; Xuan Liu (Advances in Mathematical Physics)
We present a new method for solving the fractional differential equations of initial value problems by using neural networks which are constructed from cosine basis functions with adjustable parameters. By training the neural networks repeatedly the numerical solutions for the fractional differential equations were obtained. Moreover, the technique is still applicable for the coupled differential equations of fractional order. The computer graphics and numerical solutions show that the proposed method is very effective.